Evaluation and reconditioning of donor organs for transplantation through ex vivo lung perfusion - Luis Gustavo Abdalla (Einstein (São Paulo))
ABSTRACT Objective: To assess the feasibility and impact of ex vivo lung perfusion with hyperoncotic solution (Steen Solution™) in the utilization of these organs in Brazil. Methods: In this prospective study, we subjected five lungs considered to be high risk for transplantation to 4 hours of ex vivo lung perfusion, with evaluation of oxygenation capacity. High-risk donor lungs were defined by specific criteria, including inflammatory infiltrates, pulmonary edema and partial pressure of arterial oxygen less than 300mmHg (inspired oxygen fraction of 100%). Results: During reperfusion, the mean partial pressure of arterial oxygen (inspired oxygen fraction of 100%) of the lungs did not change significantly (p=0.315). In the first hour, the mean partial pressure of arterial oxygen was 302.7mmHg (±127.66mmHg); in the second hour, 214.2mmHg (±94.12mmHg); in the third hour, 214.4mmHg (±99.70mmHg); and in the fourth hour, 217.7mmHg (±73.93mmHg). Plasma levels of lactate and glucose remained stable during perfusion, with no statistical difference between the moments studied (p=0.216). Conclusion: Ex vivo lung perfusion was reproduced in our center and ensured the preservation of lungs during the study period, which was 4 hours. The technique did not provide enough improvement for indicating organs for transplantation; therefore, it did not impact on use of these organs.